Dietary docosahexaenoic acid supplementation inhibits acute pulmonary transcriptional and autoantibody responses to a single crystalline silica exposure in lupus-prone mice - Chauhan, Preeti S.; Benninghoff, Abby D.; Favor, Olivia K.; Wagner, James G.; Lewandowski, Ryan P.; Rajasinghe, Lichchavi D.; Li, Quan-Zhen; Harkema, Jack R.; Pestka, James J. (Frontiers in Immunology, 2024)
Workplace exposure to respirable crystalline silica (cSiO2) has been epidemiologically linked to lupus. Consistent with this, repeated subchronic intranasal cSiO2 instillation in lupus-proneNZBWF1 mice induces innate-/autoimmune-related gene expression, ectopic lymphoid tissue (ELT), autoantibody (AAb) production in the lung within 5 to 13 wk followed systemic AAb increases and accelerated onset and progression of glomerulonephritis within 13 to 17 wk. Interestingly, dietary docosahexaenoic acid (DHA) supplementation suppresses, but the underlying molecular mechanisms remain unclear.Methods: This study aimed to test the hypothesis that dietary DHA supplementation impacts acute transcriptional and autoantibody responses in the lungs of female NZBWF1 mice 1 and 4 wk after a single high-dose cSiO2 challenge. Groups of mice were initially fed a control (Con) diet or a DHAcontaining diet (10 g/kg). Cohorts of Con-and DHA-fed were subjected to a single intranasal instillation of 2.5 mg cSiO2 in a saline vehicle (Veh), while a Con-fed cohort was instilled with Veh only. At 1 and 4 wk post-instillation (PI), we compared cSiO2's effects on innate-/autoimmune-related gene expression and autoantibody (AAb) in lavage fluid/lungs of Con-and DHA-fed mice and related these findings to inflammatory cell profiles, histopathology, cell death, and cytokine/chemokine production.Results: DHA partially alleviated cSiO2-induced alterations in total immune cell and lymphocyte counts in lung lavage fluid. cSiO2-triggered dead cell accumulation and increased levels of inflammation-associated cytokines and IFN-stimulated chemokines were more pronounced in Con-fed mice than DHA-fed mice. Targeted multiplex transcriptome analysis revealed substantial upregulation of genes associated with autoimmune pathways in Con-fed mice in response to cSiO2 that were suppressed in DHA-fed mice. Pathway analysis indicated that DHA inhibited cSiO2 induction of proinflammatory and IFN-regulated gene networks, affecting key upstream regulators (e.g., TNFα, IL-1β, IFNAR, and IFNγ). Finally, cSiO2-triggered AAb responses were suppressed in DHA-fed mice.Discussion: Taken together, DHA mitigated cSiO2-induced upregulation of pathways associated with proinflammatory and IFN-regulated gene responses within 1 wk and reduced AAb responses by 4 wk.